Examining e-loyalty towards online shopping platforms: The role of coupon proneness and value consciousness. Issue 3 (5th June 2017) - Zheng, Xiabing; Lee, Matthew; Cheung, Christy M.K.
Abstract : Purpose: Existing research has long considered e-loyalty as a key to the success of online shopping. The purpose of this paper is to advance the theoretical understanding of e-loyalty by exploring the roles of coupon proneness and value consciousness in the context of online shopping platforms. Design/methodology/approach: The authors empirically tested the research model using a sample of 537 users of an online shopping platform in a longitudinal setting. Findings: The results provided support to all the hypotheses in the research model; particularly, the authors found that coupon proneness and value consciousness play important roles in explaining e-loyalty. They both exhibited significant moderating effects on the relationship between loyalty intentions and repurchase behaviors. The impact of trust on loyalty intentions was also examined. Research limitations/implications: The authors believe that this study will shed light for practitioners and enable researchers to deepen their understanding of e-loyalty in online shopping platforms. Originality/value: The research better explains the gap between two important price-tactics-related variables (including coupon proneness and value consciousness); and further examines their roles in determining customers' repurchase behaviors in the context of online shopping, which is not well examined in previous studies.